Local Superior Products in Fishery Sector in Banggai Regency Indonesia - Layoo, Nurhidayah; Rahman, Wahyudin; K. Djawa, Sutrisno; Mambuhu, Nurmawati; Sukari Agustina, Sri; ., Tasruddin; Diana Khartiono, Lady; Wuniarto, Erwin; Samaduri, Lutfi; Kurniasih, Nuning (International Journal of Engineering and Technology, 2018)
The fisheries sector is one of the prima donna of Banggai Regency because the maritime and fisheries sector development is mentioned in the vision statement of the Banggai Regency Government.The purpose of this research was to determine superior local products in the sub-sector of the processing industry of Banggai Regency Indonesia by using Analytic Hierarchy Process (AHP) approach. This research aims to determine the superior local product in the fishery sector of Banggai Regency Indonesia with the Analytic Hierarchy Process (AHP) approach and supported by Expert Choice 11 software. The research was conducted based on several criteria such as production facility availability, market potential, human resource support, uniqueness, and economic contribution. The data were taken by purposive sampling method by considering the capacity and ability of respondentsÂ  consisted of 15 SMEs stakeholders in fishery sector, 12 heads of division in Fisheries and Marine Affairs Department, and 7 academics in Faculty of Fishery, and 5 Faculty of Economics. The data were collected through Focus Group Discussion (FGD) and in-depth interview. The result shows that the priority of superior local products of Banggai Regency can be developed by the local government namely wild fisheries products (pelagic fish species). In addition, the emphasis in aspects of human resources and means of production facilities.Â